2016
DOI: 10.1681/asn.2015080953
|View full text |Cite
|
Sign up to set email alerts
|

Combined Assessment of Phospholipase A2 Receptor Autoantibodies and Glomerular Deposits in Membranous Nephropathy

Abstract: Serum phospholipase A2 receptor antibodies (SAbs) and glomerular phospholipase A2 receptor antigen (GAg) deposits have been observed in idiopathic membranous nephropathy (IMN). However, the clinical application of these two biomarkers, particularly GAg deposition, needs to be further evaluated. We measured SAb concentration by ELISA and GAg deposition by immunofluorescence in 572 patients with biopsy-proven IMN. Overall, 68.5% of patients (392 of 572) had detectable SAb (SAb+), and 98.7% of patients who were S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
63
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 24 publications
(38 reference statements)
10
63
1
1
Order By: Relevance
“…We then faced the question on whether the 2 lesion profiles were linked or not. Beck et al [12] as well as others [13] showed that ∼ 70% of patients with idiopathic MN have antibodies against PLA2R while secondary forms are predominantly serum negative, as verified in our patient. In this scenario, the likelihood is that the MN profile followed a secondary cause.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We then faced the question on whether the 2 lesion profiles were linked or not. Beck et al [12] as well as others [13] showed that ∼ 70% of patients with idiopathic MN have antibodies against PLA2R while secondary forms are predominantly serum negative, as verified in our patient. In this scenario, the likelihood is that the MN profile followed a secondary cause.…”
Section: Discussionsupporting
confidence: 86%
“…A patient presenting with sudden nephritic syndrome, history of unprotected sex habits, and very high levels of VDRL and FTAbS has been described [13] . In our patient, despite no other clinical signs of syphilis and very low serologic titles, one cannot fully exclude the Treponema antigen as the primary cause of this immuno-complex nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that the risk of relapse should be carefully monitored in the first year after attainment of a PR. Previous studies reported that patients with a sustained positive glomerular or serum PLA2R antibody deposition had a high risk of relapse [23,27] . According to Beck et al [28] , the high relapse risk for patients with only a PR may be due to a residual immunological disease in spite of the reduction of proteinuria.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, PLA2R antibodies have also been reported to be of prognostic significance. Patients with positive PLA2R antibody titres at the time of biopsy have a lower rate of complete remission 14. Decreasing antibody titres suggest immunological remission which is generally followed by remission of proteinuria 15 16.…”
Section: Autoimmune Pathogenesismentioning
confidence: 99%